Prevalence and Factors Associated with Anxiety among Midwifery Students in Central Java Province during the COVID-19 Pandemic - Wijayanti, Feri Anita; Agussafutri, Wahyu Dwi; Umarianti, Tresia; Andhikatias, Yunia Renny; Widyastutik, Desy; Meilawati, Nanda (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2022)
Introduction: The government has issued ‘the adaptation to new habits’ policy as there was a rapid increase in COVID-19 cases. This study aimed to assess the prevalence of anxiety and analyze the associated factors of anxiety among midwifery students.Method: A cross-sectional study was conducted among midwifery students who are living and studying in Central Java Province from October 1 to October 25, 2020 using convenience sampling. The number of participants who met the criteria in the study was 1135. The online self-reported questionnaire was developed, which comprised sociodemographic characteristics, health-related information, and anxiety using The Zung’s Self-rating Anxiety Scale. Data were analyzed using descriptive statistics and binary logistic regression analysis with p-value <0.05 as the cut-off point for significance.Results: The prevalence of anxiety comprised of mild (9.7%), moderate (1.4%), and severe (1%), respectively. Exposure to a suspected case (OR = 2.3, 95% CI = 1.2, 4.6, p = 0.02) and age (OR = 0.4, 95% CI = 0.5, 0.9, p = 0.04) were significantly associated with anxiety. Students who were having contact with suspected COVID-19 was a 2.8 times greater risk of having anxiety. Students aged < 20 years was a 1.53 times greater risk of anxiety than those aged ≥ 20 years.Conclusions: This study reveals that exposure to a suspected case and less than 20 years old were the risk factors of a higher anxiety levels among the midwifery students. Prevention and impact reduction intervention should be conducted.